2017
DOI: 10.1007/s13730-017-0288-8
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic renal cell carcinoma to the small bowel: three cases of GI bleeding and a literature review

Abstract: Approximately 25-30% of patients with renal cell carcinoma (RCC) have metastatic disease at the time of diagnosis, where the most common sites of metastasis are the lung (50-60% of patients with metastatic disease), bones (30-40%), liver (30-40%), and brain (5%). Although RCC metastasis to the small intestine is thought to be exceedingly rare, with predominantly isolated case reports and a few case series in the literature, we present below three additional cases at our institution of metastatic RCC to the sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 17 publications
0
20
0
2
Order By: Relevance
“…A recent cohort study of over 3,000 patients described the prevalence of symptomatic small intestinal metastases from RCC as 0.71%, although post mortem studies have found a higher incidence at 2% [4, 5]. The ileum is the most common site of disease, with duodenal metastases from RCC being a much rarer phenomenon [3, 5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent cohort study of over 3,000 patients described the prevalence of symptomatic small intestinal metastases from RCC as 0.71%, although post mortem studies have found a higher incidence at 2% [4, 5]. The ileum is the most common site of disease, with duodenal metastases from RCC being a much rarer phenomenon [3, 5].…”
Section: Discussionmentioning
confidence: 99%
“…There are less than 40 cases reported in the English language literature to date. With the advent of newer treatment strategies and the resulting improved survival, the incidence of gastrointestinal metastatic disease will become more common [3]. We present a case of metastatic RCC to the duodenum which was seen recently at our institution.…”
Section: Introductionmentioning
confidence: 99%
“…This results in more time for the primary RCC to metastasise to the small bowel and become symptomatic. 5 The ways in which RCCs spread show remarkable variability, which can be haematogenous, lymphatic, transcoelomic, or by direct invasion. Given this unpredictable natural history, clinicians should thus have a low threshold for RCC metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Bis heute sind in der englischsprachigen Literatur weniger 40 Fälle dokumentiert. Mit dem Aufkommen neuer Behandlungsstrategien und dem daraus resultierenden verbesserten Überleben wird die Inzidenz gastrointestinaler Metastasen steigen [3]. In der vorliegenden Arbeit stellen wir den Fall eines Nierenzellkarzinoms mit Metastasierung ins Duodenum vor, der kürzlich in unserer Klinik aufgetreten ist.…”
Section: Einführungunclassified
“…Eine kürzlich durchgeführte Kohortenstudie mit mehr als 3.000 Patienten gab die Prävalenz von symptomatischen Dünndarmmetastasen eines RCC mit 0,71 % an, wobei die Inzidenz in Post-mortem-Studien jedoch bei 2 % lag [4, 5]. Bevorzugte Krankheitslokalisation ist das Ileum, während Duodenalmetastasen eines RCC sehr viel seltener auftreten[3, 5].…”
Section: Diskussionunclassified